(3aJM GdhgGH TQM fRgI GdCMHGHs - (3Ydj Hf CHi HcQ Hf GdLeGd GdCfUGQj GdNRQLj GdTGaYjs; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s ((3ebHhd Hf MSjf Hf Rjf GdYGHOjf GdeGdci Gdeci GdcQeGfi s)
(3ChdgG (B:s
(3CeG HYO MeOkG ddg SHMGfg hJYGdi GdhGMO Ci GdeSJMjd Ydjg bHhd GdLRi hGdEfbSGe agh YR hLd hGMO ai PGJg s
(3BNQgG (B:s
(3gPG GdbOQ caGjI ddeHJOF hef CQGO GdRjGOI Ydi Pdc ajcajg CUdg Ci GdeQTOI hGdMeO ddg ChdkG hBNQkG hXGgQkG hHGWfkG s
(3GdfSNI HgG MhGTs
(3fRgI GdMSGH GNJUQg GHf GdgGFe ef cJGH GdeSei eQTOg GdWGdH Edi Cefi GdeWGdH GfXQ cTa GdXfhfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs